THE INFLUENCE OF THE USE SIMULATION METHOD AND VIDEO MEDIA ON LEARNING OUTCOME PARTOGRAF IN NORMAL CHILDBIRTH CARE IN AKBID NUSANTARA INDONESIA LUBUKLINGGAU 2020 - Novia Sari; Arie Anggraini; Siti Qoiriyah (Sekolah Tinggi Pariwisata Mataram, 2021)
The purpose of this research was to know the influence of the use simulation method and video media on learning outcome partograf in normal childbirth care in AKBID Nusantara Indonesia Lubuklinggau 2020. It was based on problems of data obtained from the study program D III Midwifery AKBID Nusantara Lubuklinggauabout value of midwifery care II childbirth since 2018 until 2019 have decrease. This research is quasi experiment study using research method two group pretest posttest design type. The sampling in this research about 30 students.This research process have been done at 22 April-7 July 2020 at AKBID Nusantara Indonesia Lubuklinggau. Data analysis use univariat and bivariat with Willcoxon test. Based on the research concludes that there was a difference outcome partograf there was show from average value pretest (66,35) and happen increase average value posttest (76,09). Nexts used Willcoxon test available value of sig (2 tailed) was 0,002 with α 0,05. So it can be show that sig (0,002) < α (0,05) so there is a positive and significant influence of the use simulation method and video media on learning outcome partograf in normal childbirth. Thus it is expected that educational institutions particulary study program D III Midwifery AKBID Nusantara Lubuklinggaucan do variations method and media partograf in learning so that students can easily understand the material given by lecturer, will thus be able to improve the quality of human resources midwife candidates until they’re able to compete in the era of globalization.